Effect of salinity on germination and vigor of melon seeds - Aguiar, Paulo Anselmo Andrade; Pereira, José Ribamar (Pesquisa Agropecuaria Brasileira, 2014)
This research was undertaken to evaluate the germination and vigor of melon seeds (Cucumis melo L.) under different soil salinity concentrations. It was detected that concentrations up to 6.27 mmho/cm of electrical conductivity (CE25°C) did not affect germination; however, seed vigor was affected at lower concentrations. Increasing salinity levels caused higher detrimental effects to the seeds. A germination reduction higher than 50% (DL 50) and a very severe reduction in the seed vigor was noticed at CE25°C = 9.46 mmho/cm.